JARGON ON PANDEMIC ERA FOUND IN WEBSITES - Alim, Wahab Syakhirul; A`yuniyah, Kurrotun; Fadilah, Fadila (CALL, 2022)
Pandemic has created a lot of new jargons that are rarely existed before. Jargon is a special words that only used in certain field. While all of these jargons are in the form of word. As a result, this research discusses morphological analysis with an emphasis on derivational, inflectional, and word construction with the formulation of problems are: how is the morphological analysis of jargon on pandemic era found in websites and what are the meaning of each jargon on pandemic era. The aim of this research is to know the morphological analysis and the meaning of jargon on pandemic era. This research is using qualitative approach that kind of this study includes to library research. The data sources were obtained through documentation from websites like The Jakarta Post, The Washington Post, New York Times, CNN, and BBC. For the data analysis of this research used content analysis which refers to the news texts on websites. The results of this research indicate that there are 40 jargons on pandemic era that found in websites, such as 1 jargon is blending, 6 jargons are acronyms, 6 jargons are compounding, 2 jargons are derivational affixes, 5 jargons are inflectional affixes, and 20 jargons are multiple processes. Its may also be stated that while there are numerous morphological analyses of jargon throughout the pandemic era, the majority of them pertain to the multiple processes.Keywords: morphological analysis, jargon, pandemic